2016
DOI: 10.1371/journal.pone.0167772
|View full text |Cite
|
Sign up to set email alerts
|

International Collaboration Patterns and Effecting Factors of Emerging Technologies

Abstract: With the globalization of the world economy, international innovation collaboration has taken place all over the world. This study selects three emerging technologies (3D printing, big data and carbon nanotubes and graphene technology) among 20 countries as the research objects, using three patent-based indicators and network relationship analysis to reflect international collaboration patterns. Then we integrate empirical analyses to show effecting factors of international collaboration degrees by using panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 52 publications
(55 reference statements)
1
11
0
Order By: Relevance
“…A study about the global production of pairwise meta-analyses (n = 736) published by 3,178 authors from 51 countries reported that developed countries such as the USA, the UK, and Canada were the greatest producers [ 36 ]. Similar results were found in our study, but with the emergence of new countries such as China and Italy, which may change the future publication patterns of NMAs [ 37 , 38 ]. New countries may enter, probably because NMAs are a valid, cheap, and quick alternative to support pricing and marketing approval decisions, especially in the absence of direct comparisons [ 27 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 89%
“…A study about the global production of pairwise meta-analyses (n = 736) published by 3,178 authors from 51 countries reported that developed countries such as the USA, the UK, and Canada were the greatest producers [ 36 ]. Similar results were found in our study, but with the emergence of new countries such as China and Italy, which may change the future publication patterns of NMAs [ 37 , 38 ]. New countries may enter, probably because NMAs are a valid, cheap, and quick alternative to support pricing and marketing approval decisions, especially in the absence of direct comparisons [ 27 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 89%
“…The patent reflects the latest technological inventions and contains valuable information about patentees, while also providing a reliable basis for technical research (Bai, 2017). Scholars and policy makers use patent information to analyze technology trends, explore the nature, sources, and economic effects of technology, and to study the size distribution, internationalization, and technology diversification of innovative companies (Bai, 2016). The research shows that patent analysis has value in formulating national industrial development planning and internationalization strategy.…”
Section: Data and Methods Datamentioning
confidence: 99%
“…Different institutions have different innovative capabilities in different molecular technology fields of 3D printing technology. In order to fully retrieve patents of 3D printing and systematically describe the global innovational network characteristics and evolution of the 3D printing industry, this paper is based a literature research (Bai, 2016) and on three rounds of opinion by experts from the National Additive Manufacturing Innovation Center of China, and is also based on the American Society for Testing and Material (ASTM) classification standards. 3D printing technology is divided into six categories: curing technology, laser sintering and bonding technology, material melting and bonding technology, plate lamination technology, bio-printing technology and 3D food printing technology.…”
Section: Data and Methods Datamentioning
confidence: 99%
See 2 more Smart Citations